Synchronised demand-capacity balancing in collaborative air traffic flow management - Xu, Yan; Prats, Xavier; Delahaye, Daniel (Elsevier, 2020)
This paper introduces a novel approach for synchronised demand-capacity balancing within a proposed Collaborative Air Traffic Flow Management framework. The approach is aimed to realise optimising traffic flow and scheduling airspace configuration in a more harmonised manner. Options such as delay assignment and alternative trajectories (generated and submitted by Airspace Users) are intended for regulating the traffic flow. Airspace reconfiguration involves, on the other side, adjusting the opening schemes of predefined configurations, or creating new ones (if needed) through dynamic sectorisation. Results suggest that, using the proposed approach, the required system delay can be reduced remarkably, whereas the number of opened sectors (and thus operating cost) and the total capacity provision (supplied by the Air Navigation Service Providers) decrease at the same time, due to the increased capacity utilisation per operating sector.
Keywords: Air traffic flow management; Collaborative demand and capacity balancing; Trajectory options; Airspace configuration; Sectorisation